Linear predictive coding of speech - Shah, Asadullah; Shaikh, Asadullah (IIUM Press, 2011)
Linear Predictive Coding (LPC) is a mathematical (signal processing) technique used to remove the redundancy from speech signals. To remove the redundancy from speech signal, is done in 1\vo stages, first stage is to remove short term correlations form the signal and the second is to remove long term correlations. The short term and long term redundancies are modelled by digital filters very precisely. This chapter is dedicated for LPC ofspeech